Advanced Temperature-Varied ECU Fingerprints for Source Identification and Intrusion Detection in Controller Area Networks. (30th October 2020) - Tian, Miaoqing; Jiang, Ruobing; Qu, Haipeng; Lu, Qian; Zhou, Xiaoyun
Abstract : External wireless interfaces and the lack of security design of controller area network (CAN) standards make it vulnerable to CAN-targeting attacks. Unfortunately, various defense solutions have been proposed merely to detect CAN intrusion attacks, while only a few works are devoted to intrusion source identification. Demonstrated by our experimental studies, the most advanced IDS with intrusion source identification, which is based on the physical feature fingerprints of the in-vehicle Electronic Control Units (ECUs), will fail when the temperature changes. In this paper, we innovatively propose temperature-varied fingerprinting, called TVF, for CAN intrusion detection and intrusion source identification. Motivated by the remarkable observation that the physical feature of an ECU, i.e., its clock offset, changes linearly with the temperature of ECUs, the concept of temperature-varied fingerprints is proposed. Then, for a severe intrusion case, we provide an advanced TVF for further supplemented and expanded. The proposed advanced temperature-varied fingerprinting is implemented, and extensive performance evaluation experiments are conducted in both CAN bus prototype and real vehicles. The experimental results illustrate the effectiveness and performance of advanced TVF.